OVERVIEW OF CAREER CHOICES OF STUDENTS IN GARUT CITY DISTRICT - Hamidi, Muhammad Prima; Sugara, Gian Sugiana; Nugraha, Agung (Jurnal Kajian Pendidikan dan Psikologi, 2025)
Career choice is a crucial process in shaping students' future, especially at the lower secondary (SMP) and upper secondary (SMA/SMK) education levels. This study aims to provide an overview of students' career choices across Garut Kota District. Based on data collected from 794 respondents, it was found that 55% of SMP students have a social personality type and choose community service fields at 65%. Similarly, 64% of SMA students have a social personality type, with 75% choosing community service fields, and 67% of SMK students share the same personality type, with 77% opting for careers in community service. Factors such as external pressure, lack of career exploration, and limited understanding of interests and talents were identified as major obstacles. John L. Holland's RIASEC theory, which links personality types to work environments, was identified as a useful approach to help students understand their potential and align it with suitable career paths. This study recommends the importance of career guidance services at the SMP and SMA/SMK levels to map interests and talents while providing proper career direction. Such efforts can help students make well-informed career decisions that align with their individual potential.